Hubungan Lama Menderita Dengan Kualitas Hidup Penderita Stroke Di Rumah Sakit TK II Pelamonia (Window of Public Health Journal, 2025)
Stroke is a disease or functional disorder of the brain in the form of nerve paralysis (neurological deficit) due to obstruction of blood flow to the brain, which consists of signs or symptoms of loss of nervous system function. The quality of life of stroke patients is also influenced by several factors, including factors or determinants of quality of life. Therefore, this study aims to determine the relationship between the length of suffering and the quality of life of stroke patients at Pelamonia Class II Hospital, Makassar City in 2023. This type of research is quantitative research. The population of this study was all stroke patients recorded in December 2022 at the Neurology Polyclinic of Pelamonia Class II Hospital. The sampling technique was using the non-probability sampling technique with a sample size of 75 respondents selected according to the inclusion and exclusion criteria, which included factors such as age, gender, and severity of stroke. The data analysis method used bivariate analysis with the Chi-Square correlation test. The results of the study showed that there was a relationship between the length of suffering (p = 0.03) and the quality of life of stroke patients at Pelamonia Class II Hospital, Makassar City in 2023.